PTH-107 Geoepidemiology of hepatocellular carcinoma (hcc) in the island of crete. a possible role of pesticides. (22nd June 2015) - Sifaki-Pistola, D; Mantaka, A; Koulentaki, M; Samonakis, D; Karageorgos, S; Stratakou, S; Digenakis, E; Kouroumalis, E
Abstract : Introduction: Geoepidemiological data of HCC are lacking in Greece. The island of Crete has a genetically homogeneous population with minimal immigration and therefore is suitable for such studies attempting to identify a possible contribution of environmental factors in HCC. Method: We used a data base of HCC patients constructed over the past 20 years in our Unit, the reference centre for liver disease in the island. Similar data bases for chronic HCV and HBV were also used. All patients had a histological confirmation of diagnosis. Recorded data included gender, date and place of birth and place of residence for the last 15 years. The geographic area of the study comprised the four prefectures of the island of Crete. Population statistics from 1980–2010 were obtained from the Hellenic Statistical Authority. 316 HCC patients, 633 HCV and 392 HBV patients were included in the study. Time-spatial methods were applied in Gis – ArcMap 10 software. A spatial statistical test that measures spatial autocorrelation (Moran`s index) was applied at a confidence level of 95%, in order to detect any possible significant difference between the spatial distribution to place of residence. Density maps with the spatial clusters configuring the prevalence of the disease of all provinces in the island were created. Kriging Interpolation method was applied, to produce a prediction map of HCC in Crete. Results: HCV is present in pockets of high prevalence while HBV is more uniformly distributed. HCC is more prevalent in Eastern Crete. A significant spatial autocorrelation between HCC and either HCV (Moran' I=0.64, p < 0.001) or HBV (Moran' I=0.74, p < 0.001) was found as expected. However there is a discrepancy in the South East of Crete, where a higher prevalence of HCC than expected from the dispersion of HCV and HBV was observed. Prediction maps also identified this area as the main source of future HCC cases. This is an area where extensive use of pesticides in large green houses is widely practiced. Conclusion: 1) HCC is mostly found in Eastern Crete and is broadly associated with the dispersion of chronic HCV and more so with Chronic HBV. 2) In an area with widespread use of pesticides a higher than expected spatial distribution of HCC was detected. Disclosure of interest: None Declared.